FACE MIST FORMULATION OF CHRYSANTHEMUM INDICUM L. FLOWER ETHANOLIC EXTRACT, ANTIOXIDANT ASSAY, AND IN SILICO TOXICITY PREDICTION - NOVIANI, YUSLIA; HANANDHIETA, AGNES; MUMPUNI, ESTI (International Journal of Applied Pharmaceutics, 2025)
Objective: Chrysanthemum indicum Linné (L.) flower is one of the popular ornamental plants in Indonesia. It is known to contain antioxidants that are essential for protecting our skin from free radicals. The objective of this study is to perform an in silico toxicity prediction of Chrysanthemum indicum L. metabolites, to formulate the Chrysanthemum indicum L. flower ethanolic extract into a face mist preparation, and to analyze the effect of extract variations on the physical and chemical stability and antioxidant activity of face mist preparations. Methods: The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay; toxicity prediction was performed with the pkCSM Website. The extract was formulated into face mist preparations with 0.4, 0.6, and 0.8% concentrations. Furthermore, the stability of the face mist preparations was assessed through the cycling test. Finally, the data results were analyzed using a two-way Analysis of Variance (ANOVA). Results: The majority of the metabolites derived from Chrysanthemum indicum L. were found to be non-toxic. All formulations of the face mist preparation were liquid, exhibiting a color range from yellowish-brown to dark yellowish-brown, and had a rose-like scent. The formulations met the requisite specifications of specific gravity, clarity, spray dispersibility, drying time, and pH. The IC50 values of face mist preparations were 87.75±0.02 ppm (F1), 77.57±0.02 ppm (F2), and 53.51±0.03 ppm (F3). After completing the cycling test, a rise in IC50 values was observed, with the values increasing to 88.28±0.04 ppm (F1), 79.74±0.009 ppm (F2), and 56.94±0.008 ppm (F3). Conclusion: The extract concentration variation significantly affected the face mist preparation's clarity, pH, and antioxidant stability.